Unveiling Women’s Roles and Inclusion in Mexican Small-Scale Fisheries (SSF) - Solano, Neyra; Lopez-Ercilla, Ines; Fernandez-Rivera Melo, Francisco J.; Torre, Jorge (Frontiers in Marine Science, 2021)
The contributions of women to fisheries are often invisible, ignored, and unrecognized even though they represent 47% of the global fisheries workforce, especially in pre- and post-production activities. Poor data systems lead to incorrect assumptions about the gender division of labor in fisheries. This causes the role of women in fisheries to be overlooked. To evaluate the contribution of women in the value chain, a participatory methodology was implemented in three small-scale, fisheries in Mexico: California spiny lobster (Panulirus interruptus) fishery from the northern Mexican Pacific, penshell (Atrina maura) fishery from the Gulf of California, and Caribbean spiny lobster (Panulirus argus) fishery from the Mesoamerican Reef region. This study shows an unequal inclusion of men and women as members of the fishing cooperatives where only 4%, 5%, and 20% are women in spiny lobster, red lobster, and penshell, respectively, and in the distribution of direct jobs (1 out of 6.7 jobs was held by a woman). These results indicate limited opportunities for women to access leadership positions. However, the participation percentages increased dramatically when we considered the fishery system (i.e., both direct and indirect jobs), with women accounting for 43%, 21%, and 37% of the California spiny lobster, penshell, and Caribbean spiny lobster fishery workforce, respectively. Women represented 39% of the workforce in pre-production activities, 2% in production, 29% in post-production, and 56% in complementary to production. Women tended to participate in two or more activities at the same time, generally combining work, household, and community activities. The participation of women in fisheries could be equivalent to a second working day, and even when this effort is present in similarly in three fisheries, their contribution is yet to be acknowledged in order to incorporate women in decision-making. The analysis of the value chain and the fishery system provided a more realistic picture of the contribution of women to fisheries than an analysis focused solely on extraction. This work further analyzed the importance and degree of participation of women in fishing cooperatives and the decision-making process. Strategies to reduce gender disparity are needed to encourage inclusion of women in fisheries decision-making.